Stock Index Futures Rollover Strategies : An Empirical Study of Four Countries - Slivka, Ronald T.; Qin, Han; Ye, Kai (Indian Journal of Finance, 2018)
Despite dominating transaction volume near expiration, futures rollover transactions have been little studied in developed markets or in developing markets. In this study, daily intra-market stock index futures calendar spread data for the U.S., UK, India, and China markets covering 2016 expirations formed the basis for comparing two commonly employed rollover strategies with newly devised optimal strategies based upon maximizing spread liquidity or minimizing volatility. For large positions, the optimal strategy consistently outperformed standard practitioner strategies in all four markets. For smaller initial futures positions, no performance differences between strategies were expected or found. The study also discussed practical guidelines for rolling futures positions and further research directions.